2003
DOI: 10.1002/eji.200324128
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 is essential for clearance of Leishmania major: possible role for lipophosphoglycan and Toll‐like receptor 2 signaling

Abstract: Leishmania major is an obligate intracellular eukaryotic pathogen of mononuclear phagocytes. Invasive promastigotes gain entry into target cells by receptor-mediated phagocytosis, transform into non-motile amastigotes and establish in the phagolysosome. Glycosylphosphatidylinositol-anchored lipophosphoglycan (LPG) is a virulence factor and a major parasite molecule involved in this process. We observed that mice lacking the Toll-like receptor (TLR) pathway adaptor protein MyD88 were more susceptible to infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
302
0
19

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(343 citation statements)
references
References 53 publications
(55 reference statements)
16
302
0
19
Order By: Relevance
“…The cytokines promotes an up-regulation of the TLR2 to maintain a continuous inflammatory response by unknown mechanism 9 . Our results are similar to those obtained in experimental models of L. major in mice 4,6,8 . Lipophosphoglycan, a polymer of repeating Galβ1-4Manα-PO 4 units and a prominent Leishmania surface glycoconjugate 14 , activates both mouse macrophages and human NK cells through TLR2 4,6 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The cytokines promotes an up-regulation of the TLR2 to maintain a continuous inflammatory response by unknown mechanism 9 . Our results are similar to those obtained in experimental models of L. major in mice 4,6,8 . Lipophosphoglycan, a polymer of repeating Galβ1-4Manα-PO 4 units and a prominent Leishmania surface glycoconjugate 14 , activates both mouse macrophages and human NK cells through TLR2 4,6 .…”
Section: Discussionsupporting
confidence: 91%
“…In our study, TLR2 was expressed only by macrophage in the double immunostaining. Macrophage is the most important cell in the cutaneous leishmaniasis and several studies demonstrated that TLR2 is expressed at the surface of this cell 6,8,12,13 . The absence of TLR2 in other cells can be associated with the phase of the disease, because DC and NK cells decrease in this period of the leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were previously reported in DCs infected with L. mexicana pro-and amastigotes (Bennett et al, 2001). A possible explanation for differential responses of DCs to these two stages of parasites forms is that lipophosphoglycan (LPG), the major surface molecules on promastigotes, can activate the TLR2-mediated signaling and, further, the near absence of LPG on amastigotes is responsible for the lack of DC activation (Beverley and Turco, 1998;de Veer et al, 2003). However, it is also possible that intracellular amastigotes have evolved additional strategies to down-regulate key molecules (e.g.…”
Section: Discussionsupporting
confidence: 78%
“…The few TLR activators described for Leishmania are expected to be part of the extracellular products. Lipophosphoglycan (LPG) is a TLR2 agonist capable of activating mouse macrophages and human NK cells, in a MyD88-dependent manner [4244]. Also, glycosylphosphatidylinositol, that in T. cruzi activates TLR2 and TLR4 [4547], might be a PAMP present among Leishmania extracellular products.…”
Section: Discussionmentioning
confidence: 99%